The Adipokinetic Peptides in Diptera: Structure, Function, and Evolutionary Trends - Gäde, Gerd; Šimek, Petr; Marco, Heather G. (Frontiers in Endocrinology, 2020)
Nineteen species of various families of the order Diptera and one species from the order Mecoptera are investigated with mass spectrometry for the presence and primary structure of putative adipokinetic hormones (AKHs). Additionally, the peptide structure of putative AKHs in other Diptera are deduced from data mining of publicly available genomic or transcriptomic data. The study aims to demonstrate the structural biodiversity of AKHs in this insect order and also possible evolutionary trends. Sequence analysis of AKHs is achieved by liquid chromatography coupled to mass spectrometry. The corpora cardiaca of almost all dipteran species contain AKH octapeptides, a decapeptide is an exception found only in one species. In general, the dipteran AKHs are order-specific- they are not found in any other insect order with two exceptions only. Four novel AKHs are revealed by mass spectrometry: two in the basal infraorder of Tipulomorpha and two in the brachyceran family Syrphidae. Data mining revealed another four novel AKHs: one in various species of the infraorder Culicumorpha, one in the brachyceran superfamily Asiloidea, one in the family Diopsidae and in a Drosophilidae species, and the last of the novel AKHs is found in yet another Drosophila. In general, there is quite a biodiversity in the lower Diptera, whereas the majority of the cyclorraphan Brachycera produce the octapeptide Phote-HrTH. A hypothetical molecular peptide evolution of dipteran AKHs is suggested to start with an ancestral AKH, such as Glomo-AKH, from which all other AKHs in Diptera to date can evolve via point mutation of one of the base triplets, with one exception